2020
DOI: 10.11591/ijere.v9i4.20652
|View full text |Cite
|
Sign up to set email alerts
|

Integration of 3D printing in computer-aided design and engineering course

Abstract: Engineering students at an undergraduate level typically learn the design aspect and concept through lectures and practical sessions using computeraided software. However, the current computer-aided design and engineering (CAD/CAE) course did not expose the students to apply and relate the latest advanced technologies to solve global issues, for instance as listed in the United Nations Sustainable Development Goals (UN SDG). Therefore, an improved CAD/CAE course taken by the students of the Electrical and Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…(2) This study has shown that incorporating 3D printing technology into computer-aided design and engineering courses improves students' exposure to advanced technologies and helps them develop the skills needed to apply these technologies in practical settings. Additionally, this integration fosters critical thinking and psychomotor abilities among students, equipping them with the necessary knowledge for future challenges while also promoting an understanding of Industry 4.0 and the United Nations Sustainable Development Goals (Zaman et al, 2020) (3) This study has demonstrated that 3D modeling technology effectively meets learning objectives and significantly elevates students' levels of knowledge. Medical students, through a multimodal e-learning course, particularly using 3D models, have successfully learned and understood complex concepts, responding positively to the course content (Stunden, Zakani, Martin, Moodley, & Jacob, 2021).…”
Section: D Printingmentioning
confidence: 87%
See 1 more Smart Citation
“…(2) This study has shown that incorporating 3D printing technology into computer-aided design and engineering courses improves students' exposure to advanced technologies and helps them develop the skills needed to apply these technologies in practical settings. Additionally, this integration fosters critical thinking and psychomotor abilities among students, equipping them with the necessary knowledge for future challenges while also promoting an understanding of Industry 4.0 and the United Nations Sustainable Development Goals (Zaman et al, 2020) (3) This study has demonstrated that 3D modeling technology effectively meets learning objectives and significantly elevates students' levels of knowledge. Medical students, through a multimodal e-learning course, particularly using 3D models, have successfully learned and understood complex concepts, responding positively to the course content (Stunden, Zakani, Martin, Moodley, & Jacob, 2021).…”
Section: D Printingmentioning
confidence: 87%
“…The utilization of 3D printing expands the possibilities for an engaging and cooperative learning environment (Zaman, Mokhtar, Ibrahim, Huddin, & Beng, 2020). Students can actively participate in designing and creating models, fostering teamwork abilities and communication skills.…”
Section: D Printingmentioning
confidence: 99%
“…However, there is a variation among countries in terms of using ML [4]- [7]. The rate of adopting technology is affected by the desire of individuals to use and benefit from the technology [8]- [11]. Against this background, most of the studies focused on ML in developed and emerging economies while the use of this technology in developing countries is still under-researched [12]- [15].…”
Section: Introductionmentioning
confidence: 99%